2019
DOI: 10.1111/nep.13670
|View full text |Cite
|
Sign up to set email alerts
|

Transplant associated infections—The role of the gastrointestinal microbiota and potential therapeutic options

Abstract: Infectious complications are common following kidney transplantation and rank in the top five causes of death in patients with allograft function. Over the last 5 years, there has been emerging evidence that changes in the gastrointestinal microbiota following kidney transplantation may play a key role in the pathogenesis of transplant‐associated infections. Different factors have emerged which may disrupt the interaction between the gastrointestinal microbiota and the immune system, which may lead to infectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Another single-centre study undertaken in Canada involving 36 kidney transplant recipients who reported a two-week history of diarrhoea showed that in 30 out of the 36 cases, an infectious agent was found 23 . Thus, other mechanisms such as the role of the gastrointestinal microbiota [24][25][26] may explain the gastrointestinal symptoms reported in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Another single-centre study undertaken in Canada involving 36 kidney transplant recipients who reported a two-week history of diarrhoea showed that in 30 out of the 36 cases, an infectious agent was found 23 . Thus, other mechanisms such as the role of the gastrointestinal microbiota [24][25][26] may explain the gastrointestinal symptoms reported in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The patients in the Erpicum group received MSC treatment on D3±2 with a dose of approximately 1.5×10 6 -3×10 6 cells/kg [20] . The Sun group separately infused 2×10 6 cells/kg and 5×10 6 cells 30 min before surgery and during surgery [22] , while the Pan group chose to inject 5×10 6 MSCs during surgery, followed by 2×10 6 cells/kg on D30 [23] . The Tan group transplanted two doses of 1-2×10 6 cells/kg MSCs before surgery and on D14 postsurgery [21] .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The long-term consumption of regular immunosuppressive drugs, including corticosteroids, calcineurin inhibitors (CNIs), antimetabolites, and sometimes lymphodepletion, can signi cantly increase the risk of some important adverse effects, such as nephrotoxicity, infection, tumorigenicity, diabetes and cardiovascular diseases, which can affect the long-term graft outcomes and can even sometimes be lifethreatening [1][2][3][4][5] . Infectious complications are common following KT and rank among the top ve causes of patient deaths with allograft function [6] . Despite great efforts in drug innovations, the drawbacks mentioned above have not yet been resolved, and the hazards affecting long-term graft survival have failed to substantially decrease [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Interest regarding the relationship between the gastrointestinal microbiota and chronic diseases, such as diabetes mellitus, obesity and chronic kidney disease, has surged over the last 5 years 1‐6 . In the setting of kidney transplantation, changes in the gastrointestinal microbiota are hypothesized to be associated with various infections, 7‐10 but evidence to address the hypothesis is scant. In comparison, a longitudinal study of the gut microbiota from 38 liver transplant recipients at Kyoto University Hospital in Japan between June 2013 to September 2014, reported the relative abundance of Staphylococcus aureus , Enterococcus faecium , Escherichia coli and Pseudomonas aeruginosa were elevated in those acquiring bloodstream infections 11 .…”
Section: Introductionmentioning
confidence: 99%